Addressing social innovation in the Malaysian University-Industry-Community knowledge transfer partnership: A preliminary empirical insight. - Jali, Muhamad Nizam; Abas, Zakaria; Ariffin, Ahmad Shabudin (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2016)
The aim of this paper is to give a preliminary empirical insight on the potential impact of strategic knowledge management processes, i.e. knowledge creation, knowledge transfer and knowledge application, on social innovation as a new innovation outcome strategy within the Malaysian university-industry-community knowledge transfer partnership. Based on survey of relevant literatures and the gaps discovered, a research framework is then proposed. The processes of knowledge creation, knowledge transfer and knowledge application is proposed as independent variables. Social innovation is the dependent variable of the study. The preliminary empirical data was generated through structured questionnaires. The project leaders of the selected samples of Malaysian university-industry-community knowledge transfer partnership projects were chosen to answer the questionnaires distributed. The findings of this study show that all variables items are well above the acceptable level of construct reliability which is determined by the Cronbach’s Alpha value. Furthermore, the descriptive analysis also shows that respondents were consistent in their responses to the measurement items used as the independent and dependent variables in the framework of this study.